2009
DOI: 10.1177/070674370905401202
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy: Assessment and Forensic Implications

Abstract: Psychopathy was the first personality disorder to be recognized in psychiatry. The concept has a long historical and clinical tradition, and in the last decade a growing body of research has supported its validity. 1, p 28 I n the decade following this 1998 statement, the theoretical and empirical literature on psychopathy has expanded virtually at an exponential rate, with the addition of well over 500 scientific publications and many books and edited volumes. Much of this literature examines and evaluates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
135
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(152 citation statements)
references
References 130 publications
(196 reference statements)
7
135
0
10
Order By: Relevance
“…Although original conceptualizations of psychopathy acknowledged that criminality was not necessarily a correlate (Cleckley 1941), a majority of research has nevertheless focused on incarcerated or clinical Successful Psychopathy and Unethical Decision-Making 141 populations. As a result, such studies have often found psychopathy to be related to violent criminal behavior (Cornell et al 1996;Hare and Neumann 2009;Salekin et al 1996), high rates of recidivism (Hemphill 1998), and misbehavior in institutional settings (Hill et al 2004). Although such studies confirm what the general public perceives psychopathy to be in terms of criminality (Furnham et al 2009), the findings fail to capture the range of behaviors that may be exhibited by successful psychopaths, who by definition have typically avoided the type of extreme actions that lead to institutionalization or incarceration.…”
Section: Psychopathy and Unethical Decisionsmentioning
confidence: 98%
“…Although original conceptualizations of psychopathy acknowledged that criminality was not necessarily a correlate (Cleckley 1941), a majority of research has nevertheless focused on incarcerated or clinical Successful Psychopathy and Unethical Decision-Making 141 populations. As a result, such studies have often found psychopathy to be related to violent criminal behavior (Cornell et al 1996;Hare and Neumann 2009;Salekin et al 1996), high rates of recidivism (Hemphill 1998), and misbehavior in institutional settings (Hill et al 2004). Although such studies confirm what the general public perceives psychopathy to be in terms of criminality (Furnham et al 2009), the findings fail to capture the range of behaviors that may be exhibited by successful psychopaths, who by definition have typically avoided the type of extreme actions that lead to institutionalization or incarceration.…”
Section: Psychopathy and Unethical Decisionsmentioning
confidence: 98%
“…While there is still substantial debate on the status of antisocial behavior being either an integral part of the psychopathy construct (Hare and Neumann, 2009) or rather a consequence of its other features (Cooke and Michie, 2001), recent studies have converged on a three-factor model of the psychopathic personality, consisting of callous-unemotional, grandiosemanipulative and impulsive-irresponsible traits (Cooke and Michie, 2001;Salekin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the PCL-R (Hare, 2003) is one of the most widely used and respected measures with considerable research supporting its reliability and validity (Hare & Neumann, 2006;Skeem, Polascheck, Patrick, & Lilienfeld, 2011). Considered by some to be the gold standard for assessing psychopathy (Hare & Neumann, 2010), there are various strengths and weaknesses to this commonly used assessment. Reviewing information across a lifespan and from a range of sources, the PCL-R offers a comprehensive review of an individual's functioning.…”
Section: Assessing Psychopathymentioning
confidence: 99%